A statistical quality control study Cosmos Bottling Corporation - Abrena, Jasmin; Ang, Sheila; Escudero, Ma. Bernadette; Nerida, Kristine (College of Engineering, 1999)
Cosmos Bottling Corporation is the second largest bottling company in the country today after eight decades of softdrink manufacturing. It is known for its products Pop cola, Sarsi, Jolt Cola and Sunkist. Of its many plants in the country, the group decided to hold the statistical study in the bottling operation of Pop Cola in the Valenzuela plant. The Quality Assurance Department pointed out three problem areas on which the group should concentrate on. These are low fill, high fill and uncapped bottles. The weight of these problems on the production process of the company is concluded using Failure Mode and Effects Analysis and Pareto Analysis. The group aims to perform a statistical quality control study on these areas in order to improve the production of the company using Quality Improvement Tools. One of the techniques used is the Cause and Effect diagram which aids in establishing the contributing factors and their relationship with the problem areas of Cosmos Bottling Corporation. Control Charts were also used in order to monitor the stability of the bottling process and the trends in the conditions of the aforementioned problem areas. Another tool used is the design of experiments which identified whether varying the temperature indeed causes the low-filled products. Lastly, a comparison of the cost of operation and cost of replacement of the current machines were made. At the conclusion of the study, the group came up with several recommendations on the plant's bottling process. The group suggests a scheme that would monitor the number of defective units by utilizing an evaluation sheet for the refrigeration system. Also, further study on the variability of the process and the replacement of current machines is recommended by the group.